Association of Postoperative Slip Reduction With Patient-Reported Outcomes at Two Years After Fusion Surgery for Low-Grade Degenerative Spondylolisthesis: A Single-Center Study - Tom Folkerts; Julia Wimmer; Lukas Schönnagel; Anna-Maria Mielke; Bruno Verna; Pedro Rocha Torres; Paul Köhli; Jiaqi Zhu; Jennifer Shue; Rolando Duculan; Andrew A. Sama; Federico P. Girardi; et al. (Global Spine Journal, 2026)
Study Design Retrospective cohort study of prospectively enrolled patients. Objectives To evaluate the association between postoperative slip reduction and improvement in disability and low back pain (LBP) after lumbar fusion for low-grade degenerative spondylolisthesis (DLS), and to determine whether outcomes are independently associated with slip reduction or with sagittal alignment changes. Methods 160 patients undergoing lumbar fusion for low-grade DLS were analyzed. Slip reduction was quantified on lateral radiographs as absolute change in relative slippage normalized to vertebral body dimensions. Disability and LBP were assessed using the Oswestry Disability Index (ODI) and numeric rating scale (NRS) preoperatively and at two years. Associations between slip reduction and improvement in ODI and LBP were analyzed using multivariable linear regression adjusted for demographics, baseline symptoms, fusion length, and preoperative slippage. Results Slip reduction was independently associated with greater improvement in ODI and LBP (both p0.05). Conclusions Postoperative slip reduction was independently associated with greater improvement in disability and LBP among patients undergoing lumbar fusion with attempted reduction for low-grade DLS, whereas associated changes in sagittal alignment were not. However, given the moderate explanatory power of the regression models, slip reduction should be interpreted as one of several factors associated with postoperative outcomes. As this was an observational analysis, residual confounding by indication cannot be excluded, and prospective validation is warranted to further define the role of slip reduction in surgical decision-making.